Bahasa Indonesia Sebagai Alat Pemersatu Mahasiswa dari Beragam Daerah di Prodi KPI Kelas B - Wanda Amelia Putriyani; Najma Zahira Farhan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the role of Indonesian as an integration tool between students with different regional language backgrounds in Class B of the Islamic Communication and Broadcasting Study Program (KPI) of the Islamic University of Bandung. The diversity of student cultures and regional languages presents challenges in creating effective communication in the campus environment. Indonesian, as a regional language and the language of instruction in education, plays an important role in encouraging interaction between students who are different from their mother tongue. This study uses a qualitative approach with interview and observation methods to find out the experiences and views of KPI Class B students regarding the use of Indonesian in communication both in academic and social contexts. The results of the study show that despite communication difficulties due to differences in accent and language fluency, Indonesian remains an effective unifying tool to facilitate interaction and create harmony between Masu students. This study also identifies the challenges faced by students and provides suggestions for the campus to improve the Indonesian language skills of its students so that they can better support communication in the academic environment. Thus, the Indonesian language has proven to play a very important role in creating an inclusive and harmonious atmosphere among students studying various regional languages at the Islamic University of Bandung.